SEEDS BANK OF BOTANICAL GARDEN OF CHECHEN STATE UNIVERSITY - R. S. Erzhapova; M. Kh. Alikhadzhiev; R. S. Akhmatova; T. S. Khasanov (Юг России: экология, развитие)
Abstract. One of priorities of seed laboratory is creation of collection of seeds of wild plants, conservation of flora gene pool of the Chechen Republic, neighboring areas and biological diversity of flora of the Caucasus. Inventory data of seed bank of "Seed Laboratory" of Department of Botany of Chechen State University (seeds from botanical gardens, natural habitat of the Chechen Republic and adjacent areas) is the basis of this work. Currently, there are more than 350 species, representatives of more than 70 families in the collection.